An Experimental Study of Vertebrate Scavenging Behavior in a Northwest European Woodland Context. Issue 5 (10th March 2014) - Young, Alexandria; Stillman, Richard; Smith, Martin J.; Korstjens, Amanda H.
Abstract Vertebrate scavengers can modify surface deposited human remains which can hinder forensic investigations. The effects of such scavenging vary between species and regions. Published research into the effects of the scavenging of human remains is dominated by work from North America with few studies covering Northwestern Europe. Forensic scientists, investigators, and police search officers in Northwestern Europe are often left questioning on a basic level as to which scavengers are active and how they might affect human remains. This paper presents the results of a field study utilizing deer (Cervus nippon; Capreolus capreolus) as surface deposits observed by motion detection cameras in a British woodland. The most common avian and rodent scavenger species recorded included the buzzard (Buteo buteo), carrion crow (Corvus corone), wood mouse (Apodemus sylvaticus), and gray squirrel (Sciurus carolinensis). The scavenging behaviors observed were affected by seasonality, rates of decomposition, and insect activity. Scavenging by buzzards, unlike carrion crows, was most frequent during fall to winter and prior to insect activity. Overall, avian scavengers modified and scavenged soft tissue. Rodents scavenged both fresh and skeletonized remains with gray squirrels only scavenging skeletal remains. Wood mice were most active in winter and scavenged both soft tissue and bone.